(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
If the science of jurisprudence has passed through several stages from its previous development to the present day, there have certainly been disagreements and disagreements among jurists or sects in these stages of development. Of course, there are reasons and circumstances that require it. This article talks about some cases of conflict in the science of jurisprudence